Bibliometric Analysis of Indian Journal of Pure and Applied Mathematics (1998-2012) - Narang, Asha; Singh, Sukhdev (Journal of Information and Knowledge, 2014)
Bibliometric analysis of 15786 citations appended to 1310 articles published in Indian Journal of Pure and Applied Mathematics (IJPAM), in volumes 29 (1998) to 43 (2012) has been carried out to observe the distribution of contributions, authorship pattern, geographical distribution of contributions, citation analysis and the number of pages used in each volume under study. Analysis of data reveals that the number of contributions increased upto volume 32 and is decreasing since then. Joint authorship is predominant. Foreign contributors are more than the Indian contributors, journal articles are the most cited documents and university teachers form the biggest chunk of contributors. IJPAM reached the pinnacle of its glory in volume 32 and 33 after which that the growth and popularity of IJPAM is showing a downward trend.